Spazi a gestione comune nella Puglia centrale tra xi e xiii secolo: il caso della controversia tra Bitetto e Grumo - Francesco Violante (Casa de Velázquez, 2021)
This work aims to show some elements of the evolution of the land system under common management between the 11th and 13th centuries, analyzing a geographically well-defined case study (the Murge plateau in central Apulia) and following its events in a complex documentary dossier produced for over two centuries. The dynamism of rural communities in the management of large still sparsely populated territories, with a weakened structure of land ownership and in the context of the crisis of the Byzantine power, gradually clashes with the Norman mutation and then with the definitive affirmation of the monarchical power.